Investment In The Qur'an: A Thematic Interpretation Approach Based On Sharia Economic Principles - Karmila, Yusri; Yusuf, Muhammad; Mujahid, Ahmad; Supatminingsih, Tuti (Imara: Jurnal Riset Ekonomi Islam, 2024)
Background. Along with the development of the global sharia investment market, guidance based on the values of the Qur'an is needed to ensure that investments are carried out in accordance with the principles of sharia ethics. Many modern investment practices are contrary to sharia values, such as speculation, usury, or uncertainty (gharar). This study can be a guide for Muslim investors. with a thematic interpretation approach to the verses of the Qur'an related to investment can provide a deeper understanding of investment practices.Purpose. The aim of this research is to determine investment in the Al-Qur'an through thematic interpretation based on sharia economic principles.Method. The research method used is a qualitative research method. Qualitative research allows researchers to deeply and comprehensively understand the concepts contained in the Koran and sharia economic principles.Results. The Several verses that are relevant to investment are 1) The assets invested in will be multiplied by Allah SWT in QS Al-Baqarah (2) verse 261. 2) Investment as a form of lending in QS Al-Baqarah (2) verse 245. 3) Investment is a muamalah activity, which is explained in QS An Nisa (4) verse 29. 4) The principle of investment is to help in QS Al Maidah (5) verse 2. 5) and prepare for possibilities that will occur in the future by investing, QS Al Hashr (59) paragraph 18.Conclusion. This study has it is necessary to pay attention to the principles of sharia that need to be adhered to when investing. Like the principles in sharia economics, namely implementing justice, honesty, transparency, and avoiding usury or interest which is considered haram in Islam and it is very important to pay attention to investment strategies, as a form of benefit to society and worship of Allah SWT in generating investment profits